Resepsi Mahasiswa Komunikasi di Jakarta Mengenai Isi Pesan Disfungsi Keluarga Dalam Lagu “Berakhir di Aku” Karya Idgitaf - Fanny Amelia Putri; Dini Wahdiyati; Andys Tiara (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
Music as a medium of communication is used as a medium to voice social phenomena that occur in society, including the issue of family dysfunction. The song “Berakhir di Aku” by Idgitaf, which is the soundtrack of the movie Home Sweet Loan, raises the issue of family dysfunction that is relevant to today's social reality. Using qualitative research methods and Stuart Hall's reception analysis method. This study found that the song triggered deep reflection on family dynamics and the importance of social support among communication students in Jakarta, who are vulnerable to this issue.  The reception of messages related to family dysfunction is influenced by factors of cultural identity, environment, experience and parenting background of each receptor. The results identified three categories of reception: dominant hegemonic position (full acceptance of message content). Audiences in the Negotiated position category (partial acceptance of the message content). Audiences in the opposition position category (rejecting the content of the message). This difference in acceptance is based on the personal experience of each communication student in Jakarta regarding the issue of family dysfunction.